An Analysis of the use of metaphor in song lyrics on ANRI's album Timely! - Wisnu Dwi Mulyanto; Yoyok Nugroho (Universitas Dian Nuswantoro, 2026)
This study aims to analyze the use of conceptual metaphors in the lyrics of ANRI's album